Detection of choline transporter-like 1 protein CTL1 in neuroblastoma x glioma cells and in the CNS, and its role in choline uptake - Machová, Eva; O'Regan, Seana; Newcombe, Jia; Meunier, François-Marie; Prentice, Joanna; Dove, Rosamund; Lisá, Věra; Doležal, Vladimír (Journal of neurochemistry, 2009)
Choline is an essential nutrient necessary for synthesis of membrane phospholipids, cell signalling molecules and acetylcholine. The aim of this study was to detect and characterize the choline transporter-like 1 (CTL1/SLC44A1) protein in CNS tissues and the hybrid neuroblastoma x glioma cell line NG108-15, which synthesizes acetylcholine and has high affinity choline transport but does not express the cholinergic high affinity choline transporter 1. The presence of CTL1 protein in NG108-15 cells was confirmed using our antibody G103 which recognizes the C-terminal domain of human CTL1. Three different cognate small interfering RNAs were used to decrease CTL1 mRNA in NG108-15 cells, causing lowered CTL1 protein expression, choline uptake and cell growth. None of the small interfering RNAs influenced carnitine transport, demonstrating the absence of major non-specific effects. In parental C6 cells knockdown of CTL1 also reduced high affinity choline transport. Our results support the concept that CTL1 protein is necessary for the high affinity choline transport which supplies choline for cell growth. The presence of CTL1 protein in rat and human CNS regions, where it is found in neuronal, glial and endothelial cells, suggests that malfunction of this transporter could have important implications in nervous system development and repair following injury, and in neurodegenerative diseases.
Keywords: Organic Cation Transport Proteins; proteiny přenášející organické kationty; Animals; Neurogenesis; gliom; Rats; Hybridomas; cholin; Cell Line, Tumor; Protein Structure, Tertiary; CD antigeny; Choline; neurogeneze; acetylcholin; Immunohistochemistry; terciární struktura proteinů; buněčná diferenciace; zvětšování buněk; lidé; malá interferující RNA; neurony; messenger RNA; Glioma; imunohistochemie; RNA, Messenger; Humans; Antigens, CD; Neurons; Down-Regulation; Cell Enlargement; Acetylcholine; RNA, Small Interfering; krysa rodu Rattus; Neuroblastoma; Antibody Specificity; Cell Differentiation; stimulanty centrálního nervového systému; specificita protilátek; down regulace; neuroblastom; zvířata; buněčná membrána; Central Nervous System Stimulants; nádorové buněčné linie; Cell Membrane; hybridomy